Impact of Credit Rating on Capital Structure Decision: Evidence from China - Xu, Xinyi (2018)
Even the discussion about the determinants of capital structure has developed for decades, it is until recent that the attention has been extended from demand side effects to supply side effects. This paper examines impact of credit rating as an important supply side determinant on capital structure in Chinese market. My sample data consists of the 42 rated listed companies over the ten-year period from 2008 to 2017. Through using quantitative research method including multivariate analysis, pooled ordinary least squares regression and logistic regression, I confirm that firm with credit rating and the consequent access to public bond market have higher leverage ratio than their unrated counterparts. While with respect to the impact of different rating level and the potential rating change, there is no statistically significant evidence to support their correlation with capital structure.